Stent-assisted coiling of unruptured intracranial aneurysms with wide neck - Papadopoulos, Filippos; Antonopoulos, Constantine; Geroulakos, George (Asian Journal of Neurosurgery, 2020)
Objective: Morbidity and mortality in patients experiencing the rupture of intracranial aneurysm ruptures are high. We conducted a systematic review and meta-analysis to investigate the role of stent-assisted coiling (SAC) for unruptured intracranial aneurysms (UIAs) with wide neck. Materials and Methods: The current meta-analysis was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pooled proportions with 95% confidence intervals (CIs) of ten outcomes of interest were calculated. Results: We finally reviewed 13 studies, including 976 patients. The technical success of the method was 98.43% (95% CI: 95.62–99.95). Early outcomes included total periprocedural obliteration with a rate of 50.20% (95% CI: 36.09–64.30) and periprocedural rupture with zero rate. During the follow-up period, ranging from 6 months to 2 years, the total postprocedural obliteration rate was 63.83% (95% CI: 45.80–80.18) and the overall late rupture rate was 0.41% (95% CI: 0.00–2.38). The pooled in-stent stenosis rate was calculated at 1.24% (95% CI: 0.02–3.63). We also estimated a pooled rate of 0.02% (95% CI: 0.00–0.51) and 4.33% (95% CI: 2.03–7.23) for total mortality and overall neurological complications, respectively. A pooled rate of 3.94% (95% CI: 1.48–7.33) was found for stroke. Finally, the recanalization rate was recorded at 7.07% (95% CI: 4.35–10.26). Conclusions: SAC of UIAs with wide neck seems to be a safe and acceptable alternative to surgical clipping. Although early results concerning total periprocedural obliteration may be modest, follow-up outcomes may be indicative of adequate occlusion of treated UIAs.
Keywords: Intracranial aneurysm; stent-assisted coiling; wide neck